El Sid Saint Vicious - Dalton, David 1945- (St. Martin's Press, 1997)
The life story of Sid Vicious of the Sex Pistols. "Stripped of all the confusing attributes--dexterity, talent, sanity--Sid Vicious embodied rock's primal impulse in its purest form. He was the ultimate rock star, unburdened by talent or compromise."--Jacket.
Keywords: Vicious, Sid; Vicious, Sid -- 1957-1979; Sex Pistols (Musical group); Punk rock musicians -- England -- Biography; Biografie